Association of six well-characterized polymorphisms in TNF-α and TNF-β genes with sarcoidosis: a meta-analysis. - Yun Feng (Public Library of Science (PLoS), 2013)
Backgrounds In this study, we aimed to investigate the association of six well-characterized polymorphisms in tumor necrosis factor alpha and beta (TNF-α and TNF-β) genes with the risk for sarcoidosis via a comprehensive meta-analysis. Methods and findings The electronic MEDLINE (Ovid) and PubMed databases covering the period from the earliest possible year to June 2013 were searched. Total 13 qualified articles including 1584 patients with sarcoidosis and 2636 controls were recruited. The data were analyzed by RevMan software, and risk estimates were expressed as odds ratios (ORs) and 95% confidence intervals (95% CIs). Analyses of the full data set failed to identify any significant association of TNF-α gene -307A (OR=1.25; 95% CI: 0.98-1.59), -1031C (OR=0.88; 95% CI: 0.71-1.1), -863A (OR=0.89; 95% CI: 0.72-1.11), -238A (OR=0.97; 95% CI: 0.71-1.32), and -857T (OR=1.14; 95% CI: 0.74-1.77) alleles, but a significant association for TNF-β 252A allele (OR=1.65; 95%CI = 1.33-2.04; P<0.00001). Under a random-effects allelic model, there was marginally significant increased risk of sarcoidosis for -307A allele among Caucasians (OR=1.25; 95% CI: 0.96-1.62; P=0.09) but not among Asians (OR=2.12; 95% CI: 0.31-14.27; P=0.44). There was a low probability of publication bias as reflected by the fail-safe number. Conclusions This meta-analysis extended previous findings on the association between the TNF-α and TNF-β genetic polymorphisms and sarcoidosis, by showing that the TNF-β gene A252G polymorphism might be a potential risk factor for the development of sarcoidosis.